Applying Digital Competence Framework in Exploiting Information for Commercialisation of Intellectual Property Rights Purposes - Van Hai, Tran (VNU Journal of Science: Policy and Management Studies; Vol 38 No 3, 2022)
Vietnam has promulgated the policy system on intellectual property based on the principle of balancing the rights of the owner and the legitimate interests of the society, in accordance with the level of economic development of the country, towards the general development trend in the global intellectual property system. However, difficulties in commercializing intellectual property rights in the digital economy are still existed. This article analyzes the barriers in the protection and enforcement of intellectual property rights leading to difficulties in commercializing intellectual property rights in the digital economy, and proposes that applying the digital competency framework in exploiting information to commercialize intellectual property rights can be a solution. Keyword: Intellectual Property; Digital Competence Framework; Information on Exploiting Intellectual Property; Commercialisation of Intellectual Property Rights.